The real options method in project management. (Journal of Economic Research & Business Administration, 2016)
The results of the first stage of SP FIID indicate the need for substantial adjustments in the development and implementation of projects included in the program. In this regard, it is proposed to introduce innovations in the process of project management. The article reveals the essence of a real option, the contents of the Black-Scholes model and binomial model and perspectives of their application in the Kazakhstan practice. The article emphasizes the need for training for these methods of managers directly involved in project implementation.
Keywords: industrialization in Kazakhstan; project management; the real options method; Black-Scholes model; the binomial model.